Anti-de Sitter → de Sitter transition driven by Casimir forces and mitigating tensions in cosmological parameters - Luis A. Anchordoqui; Ignatios Antoniadis; Dieter Lüst (Physics Letters B, 2024)
Over the last few years, low- and high-redshift observations set off tensions in the measurement of the present-day expansion rate H0 and in the determination of the amplitude of the matter clustering in the late Universe (parameterized by S8). It was recently noted that both these tensions can be resolved if the cosmological constant parametrizing the dark energy content switches its sign at a critical redshift zc∼2. However, the anti-de Sitter (AdS) swampland conjecture suggests that the postulated switch in sign of the cosmological constant at zero temperature seems unlikely because the AdS vacua are an infinite distance apart from de Sitter (dS) vacua in moduli space. We provide an explanation for the required AdS → dS crossover transition in the vacuum energy using the Casimir forces of fields inhabiting the bulk. We then use entropy arguments to claim that any AdS → dS transition between metastable vacua must be accompanied by a reduction of the species scale where gravity becomes strong. We provide a few examples supporting this AdS → dS uplift conjecture.